DAKWAAN PASAL 303 KUHP DALAM PERKARA PERJUDIAN ONLINE DIKAITKAN DENGAN PASAL 63 AYAT (2) KUHP (STUDI PUTUSAN NOMOR:1299/Pid.B/2021/PN Lbp.) - Ahmad Adiguna Rajendra (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2022)
Ahmad Adiguna Rajendra, Setiawan Noerdajasakti, Alfons Zakaria Fakultas Hukum, Universitas Brawijaya e-mail: endrodiguna@student.ub.ac.id ABSTRAK Dalam penulisan ini, penulis membahas mengenai maraknya kasus perjudian online dan penanggulangan perjudian serta ancaman hukuman yang diberikan kepada pelaku tidak pidana perjudian, dikarenakan perjudian merupakan ancaman yang nyata terhadap norma-norma sosial yang dapat menimbulkan ketegangan individual maupun ketegangan-ketegangan sosial. Kemudian Apakah penggunaan Pasal 303 KUHP dalam surat dakwaan perkara judi online Putusan nomor 1299/Pid.B/2021/PN Lbp. sesuai dengan Pasal 63 ayat (2) KUHP, dan implikasi yuridis surat dakwaan yang menggunakan ketentuan umum (lex generalis) jika terdapat ketentuan khusus (lex specialis) suatu tindak pidana seperti Ancaman pidana menjadi lebih ringan dan Surat dakwaan dinyatakan batal demi hukum. Diharapkan penelitian ini dapat bermanfaat bagi Jaksa Penuntut umum, Hakim, dan aparat penegak hukum dalam memperoses pelaku tindak pidana khususnya tindak pidana perjuadian karena Perjudian merupakan ancaman riil atau potensial bagi berlangsungnya keteraturan sosial. Dengan demikian perjudian dapat menjadi penghambat pembangunan nasional yang beraspek materiil-spiritual. Kata Kunci : Judi, Perjudian Online, Hukuman ABSTRACT This research seeks to study the reference to Article 303 of the Penal Code concerning online gambling linked with Article 63 paragraph (2) of the Penal Code. As in the Decision Number 1299/pid.B/2021/PN.Lbp, General Prosecutors charged the defendant according to Article 303 of the Penal Code over online gambling that the defendant was involved in, while Article 27 Paragraph (2) of Law concerning Electronic Information and Transactions governs online gambling. Departing from the above issue, this research aims to investigate (1) whether the reference of Article 303 of the Penal Code as in the indictment regarding online gambling as in the Court Decision Number 1299/Pid.B/2021/Pn Lbp complies with Article 63 Paragraph (2) of Penal Code and (2) what are the juridical implications of the indictment referring to the general provisions (lex generalis) in the specific provisions (lex specialis) of a criminal case. This research employed a normative method with primary, secondary, and tertiary materials and statutory and case approaches. The data were analyzed based on systematic interpretation. The research analysis results reveal that the reference to Article 303 of the Penal Code regarding the indictment on online gambling as in the court decision highlighted above is not congruent with the provision of Article 63 Paragraph (2) of the Penal Code since this article only governs conventional gambling, different from Article 27 Paragraph (2) governing online gambling. Moreover, Article 63 Paragraph (2) of the Penal Code also governs the obligation of the use of lex specialis derogat legi lex generalis. In terms of the juridical implications where the indictment referred to lex generalis with the presence of lex specialis of a crime, the sentence given can be alleviated and the indictment can be declared null and void. Keywords: Gambling, Online Gambling, Punishment